2021
DOI: 10.3390/cells10020214
|View full text |Cite
|
Sign up to set email alerts
|

Quiescence, Stemness and Adipogenic Differentiation Capacity in Human DLK1−/CD34+/CD24+ Adipose Stem/Progenitor Cells

Abstract: We explore the status of quiescence, stemness and adipogenic differentiation capacity in adipose stem/progenitor cells (ASCs) ex vivo, immediately after isolation from human subcutaneous white adipose tissue, by sorting the stromal vascular fraction into cell-surface DLK1+/CD34−, DLK1+/CD34dim and DLK1−/CD34+ cells. We demonstrate that DLK1−/CD34+ cells, the only population exhibiting proliferative and adipogenic capacity, express ex vivo the bonafide quiescence markers p21Cip1, p27Kip1 and p57Kip2 but neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…Recently, Florian M. Hatzmann et al found that approximately 3% of human SVF ASCs were positive for CD24. Furthermore, they could induce CD24 expression in hASCs using a serum-free medium without apparently activating the Hh signaling pathway [33]. These two studies indicate that CD24 may also be upregulated by other, currently non-characterized, signal transduction circuits.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Recently, Florian M. Hatzmann et al found that approximately 3% of human SVF ASCs were positive for CD24. Furthermore, they could induce CD24 expression in hASCs using a serum-free medium without apparently activating the Hh signaling pathway [33]. These two studies indicate that CD24 may also be upregulated by other, currently non-characterized, signal transduction circuits.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, in mice, only less than 1% of the SVF cells that express CD24 also display the complete cell surface marker profile of adipocyte progenitors [19]. In the human SVF, CD24-positive ASCs are also rare [33]. The properties and functions attributed to this surface protein definitively promote it as a marker of hASCs and other types of stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,79 At last, in different in vitro models of glucocorticoids and insulin-induced adipocyte differentiation, a quick temporary increase in the levels of the membranebound variant of Dlk1 was observed just after induction of differentiation, while the full-length, cleavable Dlk1 started to decrease just after induction and both became undetectable by the end of the differentiation process. [80][81][82][83] Both the initial overexpression of the membrane-bound DLK1 and the drop in the levels of secreted DLK1 play a role in adipocyte differentiation, and the switch between the two forms of DLK1 is necessary to induce a permissive state for differentiation in response to extracellular stimuli (Fig. 1B).…”
Section: Dlk1 and Stemness Modulation In Development And Tissue Regenerationmentioning
confidence: 99%